Pengaruh Penggunaan Sosial Media TikTok, Brand Image, dan Word of Mouth Terhadap Keputusan Pembelian di Klinik Kecantikan Athena Palembang - Basyasyah Salsabila; Muhammad Kurniawan; Shafiera Lazuarni (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine the influence of social media, brand image, Word Of Mouth on purchasing decisions at the Athena Palembang Beauty Clinic. This research method uses a descriptive method with a quantitative research approach. The sampling technique in this research is non-probability sampling and purposive sampling as the sample determination technique. This research also uses the Lemeshow formula, so the minimum number required in this research is 96 respondents. Data analysis uses data quality tests, classical assumption tests, and multiple linear analysis. The results of this research are that the variables social media (X1), brand image (X2) and Word Of Mouth (X3) have a positive and significant effect on purchasing decisions (Y). So the positive influence on these three variables determines purchasing decisions significantly. Based on the results of variables X1, X2 and on purchasing decisions (Y), with a percentage of 88%, meaning that the remaining 12% is influenced by variables other than the variables studied.